Detection and characterization of a divergent avian reovirus strain from a broiler chicken with central nervous system disease - Dandár, Eszter; Bálint, Ádám; Kecskeméti, Sándor; Szentpáli-Gavallér, Katalin; Kisfali, Péter; Melegh, Béla; Farkas, Szilvia L; Bányai, Krisztián (Archives of virology, 2013)
Avian orthoreoviruses have been associated with a variety of diseases in chickens, including tenosynovitis, runting-stunting syndrome, hepatitis, myocarditis, osteoporosis, respiratory diseases, and central nervous system disease. The primary objective of our study was the molecular characterization of an avian reovirus strain, T1781, which was isolated from a broiler chicken with a central nervous system disorder in Hungary during 2012. The complete genome sequence was determined using a traditional sequencing method after cell culture adaptation of the strain. Sequence and phylogenetic analyses showed that T1781 shared only moderate nucleic acid sequence identity in several genes to previously analyzed reovirus strains from chickens, and each gene formed separate branches in the corresponding phylogenetic trees. The maximum nucleotide sequence identities of strain T1781 genes to reference avian reovirus strains ranged from 79 % to 90 %. Collectively, our analyses indicated that T1781 is a divergent chicken reovirus strain. The genetic background of this and other avian reoviruses associated with various disease manifestations needs further investigation.